PENGEMBANGAN MANDATORI ZAKAT DALAM SISTEM ZAKAT DI INDONESIA - Adang Budaya; Syamsuddin Ali Nasution (Magister Hukum Sekolah Pascasarjana Unida, 2021)
Indonesia is a country with the most Muslim population in the world. According to Global religius future, at the beginning of 2020, 87% of its citizens were Muslims or around 209.12 million people. This is very potential for the development of zakat in Indonesia. Because basically, muzakki will still be there every year or month so that economic sustainability will be maintained and sustainable. Zakat has three fundamental functions, namely to purify the soul, blessing fortune and as an expression of social care for others. Zakat is a mandatory command of God to Muslims stated in the Qur'an and the Hadith of the Prophet Muhammad. The pillars of Islam as the five foundations of Islamic identity, are the driving force in increasing piety. Coupled with the six pillars of faith as a basic manifestation of our faith in Allah Subhanahu Wa Ta'aalaa. However, what remains a problem is that Indonesia, with the status of the largest Muslim country in the world, has not been able to break the zakat into a source of state income as well as taxes. Zakat is still voluntary. While the 2011 Zakat Law No. 23 concerning the Management of Zakat only requires amil and its management procedures, which must follow the guidelines of Islamic law.Keywords : Zakat; Sharia; Islamic Law.